Mycoplasma gallisepticum triggers immune damage in the chicken thymus by activating the TLR-2/MyD88/NF-κB signaling pathway and NLRP3 inflammasome - Chen, Chunli (Vet Res, 2020)
Previous studies reported that Mycoplasma gallisepticum (MG) causes immune dysregulation in chickens. However, the underlying mechanisms of immune dysregulation in chickens are still unclear. The thymus is a primary lymphoid organ where the proliferation, differentiation and selection of T-lymphocytes occur, whereas T-lymphocytes play a crucial role in innate immune responses. To evaluate the effects of MG-infection on chicken thymus, White Leghorn chickens were divided into (1) control group and (2) MG-infection group. ATPase activities were detected by commercial kits. The hallmarks of inflammation, autophagy and energy metabolism were examined in chicken thymus tissues by histopathology, transmission electron microscopy, immunofluorescence microscopy, RT-PCR and western blotting. Immunofluorescence examination revealed that the number of CD8(+) lymphocytes has significantly reduced in MG-infection group. In addition, morphological analysis revealed that MG induced inflammatory cells infiltration. The mitochondria were swollen and chromatin material was condensed in MG-infection group. The mRNA and protein expression results showed that MG-infection triggered the nucleotide-binding oligomerization domain, leucine rich repeat and pyrin domain containing 3 (NLRP3) inflammasome through TLR-2/MyD88/NF-κB signaling pathway. Meanwhile, the expressions of autophagy-related genes were reduced both at mRNA and protein level in MG-infection group. While, ATPase activities and the expression of energy metabolism-related genes were reduced in the thymus of MG-infected chickens. These results showed that MG-infection triggered inflammatory response through TLR-2/MyD88/NF-κB signaling pathway, activated NLRP3 inflammasome, reduced the level of autophagy and impaired energy metabolism, which then lead to tissue damage in chicken thymus. The data provide new insights in MG-infection-mediated immune damage and provide possible therapeutic targets for future targeted therapy.